2018
DOI: 10.1016/j.jalz.2018.06.1838
|View full text |Cite
|
Sign up to set email alerts
|

P3‐474: Automatic Detection of Linguistic Indicators as a Means of Early Prediction of Alzheimer's and of Related Dementias: A Cross‐linguistics Analysis

Abstract: in dementia, key evidence to establish its stability. The aim of the present study is to assess the temporal stability of WAT-R in patients with dementia. Methods: Thirtytwo patients with a diagnosis of dementia according to the NIA-AA (McKhann et al., 2011) CDR 1 and 2, and 34 subjects classified as normal according to a standard neuropsychological evaluation and neurological consultation has participated. The participants were assessed with a neuropsychological evaluation in two moments (interval from 1 to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Furthermore, we found a higher pronoun-to-noun ratio and interrogative-to-total pronouns ratio for our AD group across speech samples. The higher pronoun-to-noun ratio is in accordance with the findings of Khodabaksh et al (2015), Fraser et al (2016), Kavé and Dassa (2018) and Rentoumi et al (2018). Moreover, a correlation between specific types of speech samples and pronoun type was attested within the AD group.…”
Section: An Overview Of the Findings Of The Linguistic Taskssupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, we found a higher pronoun-to-noun ratio and interrogative-to-total pronouns ratio for our AD group across speech samples. The higher pronoun-to-noun ratio is in accordance with the findings of Khodabaksh et al (2015), Fraser et al (2016), Kavé and Dassa (2018) and Rentoumi et al (2018). Moreover, a correlation between specific types of speech samples and pronoun type was attested within the AD group.…”
Section: An Overview Of the Findings Of The Linguistic Taskssupporting
confidence: 91%
“…However, pronoun overuse in our data was not correlated with a working memory impairment contra Almor's Informational Load Hypothesis (ILH) and Working Memory Impairment Hypothesis (Almor et al, 1999), as well as contra Kavé and Levy (2003a). In addition, a higher pronoun-to-noun ratio was observed which corroborated the findings of Khodabaksh et al (2015), Fraser et al (2016), Kavé and Dassa (2018) and Rentoumi et al (2018). A higher pronoun-to-noun ratio was related to a naming deficit following Fraser et al (2016) and Kavé and Goral (2016).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…There has been very little prior work on multilingual or cross-lingual dementia classification. Rentoumi et al (2018) presented preliminary results suggesting that some language features from CTP samples could transfer across Greek and English, but did not report classification results. Fraser et al (2018b) studied a related task of detecting mild cognitive impairment (MCI), and found that classification results could be improved in both English and Swedish by incorporating multilingual topic modelling into the feature extraction pipeline; however, they did not consider multilingual classification directly.…”
Section: Multi-and Cross-lingual Nlpmentioning
confidence: 96%